Evaluation of the Impact of Utilizing Stock Market Simulators for Enhancing Analytical Competence: An Experiential Learning Approach - Patil, Krishnaji Sarjerao; Patil, Digvijay Satish; Gaikwad, Hemlata Vivek; Pandey, Suruchi (Journal of Engineering Education Transformations, 2025)
This research explores the impact of stock market simulators on students pursuing technical education, specifically focusing on developing analytical skills in finance. Fifty students enrolled in technical courses with finance components participated in an experimental study. Pre and post-test surveys were conducted to assess their financial analytical skills before and after exposure to a stock market simulator, specifically Money Control. The students were given 60 days to build and operate investment portfolios using acquired analytical skills. Results from the study reveal a significant positive impact on students’ analytical skills, demonstrating increased interest and motivation in utilizing stock market simulators for learning subjects like security analysis and portfolio management. The findings suggest that stock market simulators serve as valuable tools for teaching, practising, and enhancing analytical skills in finance, particularly for students pursuing technical courses.